Experimental Calibration of Sn‐Related Varshni Parameters for High Sn Content GeSn Layers. Issue 6 (12th February 2019) - Bertrand, Mathieu; Thai, Quang‐Minh; Chrétien, Jérémie; Pauc, Nicolas; Aubin, Joris; Milord, Laurent; Gassenq, Alban; Hartmann, Jean‐Michel; Chelnokov, Alexei; Calvo, Vincent; Reboud, Vincent
Abstract: From temperature‐dependent photoluminescence of a single Ge0.84 Sn0.16 sample, Sn‐related Varshni parameters are extracted and used as input parameters in an 8‐band k·p model, and predict direct bandgap energies of high Sn content GeSn alloys with concentration varying from 8% to 16%. Then, exhaustively compared are the calculated direct Γ‐valley bandgap energies to photoluminescence results of 13% and 16% Sn content alloys and to direct bandgap energies found in literature. The agreement between k·p modeling and experimental datasets is close to 3% for different strain conditions of GeSn epilayers. The outcome of this study is an 8‐band k·p model with a fixed set of parameters, the model being self‐sufficient to describe the direct bandgap of Ge1− x Sn x layers with x varying from 8% to 16% for large ranges of strain and temperature. Abstract : Sn‐related Varshni parameters are extracted from temperature‐dependent photoluminescence of a single Ge0.84 Sn0.16 sample. These parameters are used as input for an 8‐band k·p model. Modeling the tin contribution using the proposed Sn Varshni parameters predicts the direct bandgap position of GeSn alloys with Sn content varying from 8% to 16% under different strain conditions and temperatures, without any additional calibration.